Water-based chromium-free self-lubricating fingerprint-resistant coating as well as preparation method and application thereof
Through the component combination of water-based chrome-free self-lubricating fingerprint-resistant coating, the wear and corrosion resistance of galvanized steel plates during use is solved, and the effect of maintaining good appearance and performance in the deep drawing process is achieved.
Patent Information
- Application Number
- CN202510552208.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-07-25
AI Technical Summary
Traditional galvanized steel plates are prone to problems such as white rust, red rust, plating cracking and powder loss during use, which affects the appearance quality, dimensional accuracy and corrosion resistance of the formed parts. In addition, traditional chromium treatment methods bring environmental pollution and increase costs.
Water-based chromium-free self-lubricating fingerprint-resistant coating is used, and the components include compounded polyurethane resin, polyacrylic resin, silane coupling agent, filler, molybdenum, vanadium, titanium or zirconium compounds, leveling agents and scratch-resistant additives. The polyurethane resin with different elongations of break is combined with polyacrylic resin as the main film forming substance of the coating, and other components are combined to improve the adhesion, corrosion resistance and wear resistance of the coating.
It significantly enhances the wear and corrosion resistance of galvanized steel plates, and is suitable for deep-drawing processes, maintains a good appearance and excellent wear and corrosion resistance, and avoids degradation of coating performance.
Smart Images

Figure CN120365807A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of coatings, and specifically relates to an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method and application. Background Art
[0002] Galvanizing the surface of steel plates is an economical and effective anti-rust method. Approximately half of the world's zinc is used in this process. The steel plates obtained after galvanizing are called galvanized steel plates and are widely used in the automotive, building materials, household appliances, and mechanical and electrical industries.
[0003] Although the galvanized layer can improve the corrosion resistance of steel plates, problems such as white rust and even red rust are still likely to occur during use. Most galvanized steel plates also need to be stamped into shape before being put on the market. During the stamping process, due to the friction between the die and the steel plate, problems such as cracking and powder falling of the coating are likely to occur during forming, affecting the appearance quality, dimensional accuracy, and corrosion resistance of the formed parts.
[0004] In traditional technology, in order to improve the corrosion resistance and coating adhesion of metals, a treatment solution mainly containing chromic acid, dichromic acid, or their salts is usually used on the metal surface, which is called chromium treatment. However, chromium treatment will cause problems of environmental pollution and increased costs. How to enhance the wear resistance and corrosion resistance of galvanized steel plates, maintain their good appearance, and avoid further problems of poor coating performance has always troubled relevant researchers. Summary of the Invention
[0005] Based on this, this application provides an aqueous chromium-free self-lubricating fingerprint-resistant coating. When it is used to passivate the metal surface, such as the surface of galvanized steel plates, it can significantly enhance the wear resistance and corrosion resistance of galvanized steel plates, and is suitable for deep drawing processes. It can make the workpieces after deep drawing still maintain good appearance and excellent wear resistance and corrosion resistance.
[0006] The technical solution adopted in this application is an aqueous chromium-free self-lubricating fingerprint-resistant coating, which, by weight percentage, includes the following components: 15% - 32% of a compounded polyurethane resin, 10% - 23% of a polyacrylate resin, 1% - 5% of a silane coupling agent, 1% - 5% of a filler, 1% - 5% of a compound of molybdenum, vanadium, titanium, or zirconium, 0.1% - 0.5% of a leveling agent, 1% - 5% of an anti-scratch aid, and 24.5% - 70.9% of water; wherein, the compounded polyurethane resin is compounded from polyurethane resins with different elongation at break.
[0007] In one embodiment, in the compounded polyurethane resin, the relationship between the elongation at break of each polyurethane raw material and its weight percentage shows a normal distribution.
[0008] In one embodiment, the elongation at break is denoted as EB. By weight percentage of the compounded polyurethane resin, the compounded polyurethane resin comprises the following components: 2% - 20% of polyurethane with EB < 100%, 20% - 50% of polyurethane with 100% ≤ EB ≤ 200%, 20% - 50% of polyurethane with 200% < EB ≤ 300%, and 2% - 20% of polyurethane with EB > 300%.
[0009] In one embodiment, the polyacrylic resin is a copolymer, which is copolymerized from a hard monomer and a soft monomer in a weight ratio of 1: (0.2 - 5).
[0010] In one embodiment, the hard monomer is selected from one or more combinations of vinyl acetate, acrylonitrile, acrylamide, styrene, methyl methacrylate, and methyl acrylate.
[0011] In one embodiment, the soft monomer is selected from one or more combinations of ethyl acrylate, butyl acrylate, and isooctyl acrylate.
[0012] In one embodiment, the silane coupling agent is selected from one or more combinations of amino silane coupling agents, epoxy silane coupling agents, and vinyl silane coupling agents.
[0013] In one embodiment, the filler includes nano-silica.
[0014] In one embodiment, the leveling agent includes polyether-modified silicone.
[0015] In one embodiment, the anti-scratch additive is compounded from anti-scratch additives with different particle sizes.
[0016] In one embodiment, the anti-scratch additive is composed of a first anti-scratch additive with a particle size of 0.1 μm - 0.5 μm and a second anti-scratch additive with a particle size of 1 μm - 3 μm in a weight ratio of 1: (1 - 2).
[0017] In one embodiment, the anti-scratch additive is selected from one or more combinations of polyethylene, polytetrafluoroethylene, oxidized polyethylene, and silicone dispersions.
[0018] Another object of the present application is to provide a preparation method of the aqueous chromium-free self-lubricating fingerprint-resistant coating, comprising the following steps:
[0019] Mix the compounded polyurethane resin, polyacrylic resin, silane coupling agent, filler, compounds of molybdenum, vanadium, titanium, or zirconium, leveling agent, and anti-scratch additive in water.
[0020] Another object of the present application is to provide a metal material, at least one surface of which is coated with a coating formed by the water-based chromium-free self-lubricating fingerprint-resistant coating as described above.
[0021] Another object of the present application is to provide a deep-drawing workpiece, at least one surface of which is coated with a coating formed by the water-based chromium-free self-lubricating fingerprint-resistant coating as described above.
[0022] The present application has at least the following beneficial effects: Polyurethane with low elongation rate can enhance the hardness, rigidity, wear resistance, scratch resistance, chemical corrosion resistance of the coating, and can improve the adhesion between the coating and the metal substrate, and is stable and not prone to deformation or cracking, which can avoid paint peeling; while polyurethane with high elongation rate endows the coating with high elasticity, flexibility, and improves the impact resistance and deformation resistance. In the present application, polyurethane resins with different elongation at break are compounded, and together with polyacrylate resin as the main film-forming substances of the coating, they play a major role in corrosion resistance, impact resistance and wear resistance on the surface of metals (such as galvanized steel sheets). The filler has the function of supplementing the surface film-forming defects, making the fingerprint-resistant coating more complete, and also has the function of enhancing the corrosion resistance and wear resistance of the coating. Compounds of molybdenum, vanadium, titanium or zirconium and silane coupling agents are used in combination to improve the adhesion, corrosion resistance, wear resistance, scratch resistance and appearance of the coating. A leveling agent is used in combination to reduce the surface tension between the coating and the substrate and improve the flatness and appearance of the coating film. An anti-scratch aid is used in combination to endow the entire fingerprint-resistant coating with slipperiness, and further enhance the wear resistance, scratch resistance and corrosion resistance of the coating, thereby ensuring the secondary processing quality of the metal. In summary, through the synergistic cooperation of each component, the present application obtains a water-based chromium-free self-lubricating fingerprint-resistant coating with excellent comprehensive performance. When it is used to passivate the metal surface, it can significantly enhance the wear resistance and corrosion resistance of the metal substrate (such as galvanized steel sheet), and is suitable for the deep-drawing process. It can make the workpiece after deep-drawing still maintain a good appearance and excellent wear resistance and corrosion resistance. Description of the Drawings
[0023] Figure 1 It is the effect diagram of passivating a galvanized steel sheet with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 2 of the present application;
[0024] Figure 2 It is the effect diagram after the deep-drawing process of the galvanized steel sheet passivated with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 1 of the present application;
[0025] Figure 3 It is the effect diagram after the galvanized steel sheet passivated with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 1 of the present application is subjected to a salt spray test for 120 h;
[0026] Figure 4The figure shows the effect after subjecting the galvanized steel sheet workpiece passivated with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 1 of the present application to a deep drawing process and a 96-hour salt spray test in sequence; among which, Figure 4 in (A) is the effect diagram without the salt spray test, Figure 4 in (B) is the effect diagram after the 96-hour salt spray test;
[0027] Figure 5 The figure shows the effect after subjecting the galvanized steel sheet workpiece passivated with the water-based chromium-free self-lubricating fingerprint-resistant coating in Comparative Example 2 of the present application to a deep drawing process and a 96-hour salt spray test in sequence. Detailed implementation manners
[0028] The detailed implementation manners and the drawings of the present application are only for illustrative purposes and should not be construed as a limitation to the present application. The present application can be implemented in many different forms and is not limited to the embodiments described in the present application. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosed content of the present application more thorough and comprehensive.
[0029] Unless otherwise defined, all technical and scientific terms used in the present application have the same meaning as commonly understood by those skilled in the technical field to which the present application belongs. The terms used in the description of the present application in this specification are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0030] In the present application, "and / or" includes any and all combinations of one or more of the related listed items. The "including", "having", and "comprising" described in the present application are intended to cover non-exclusive inclusion. Unless a clear limiting term is used, such as "only", "consisting of", etc., another component can be added.
[0031] In the present application, "preferably", "more preferably", "more preferably", "even more preferably", etc. refer to the embodiments of the present application that can provide certain beneficial effects in certain cases. However, in the same or other cases, other embodiments may also be preferred. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not available, nor is it intended to exclude other embodiments from the scope of the present application. That is, in the present application, "preferably", "more preferably", "more preferably", "even more preferably", etc. are only used to describe the embodiments or examples with better effects, but do not constitute a limitation to the protection scope of the present application. Similarly, "further", "even further", "especially", etc. are only used for descriptive purposes to indicate differences in content, but should not be construed as a limitation to the protection scope of the present application.
[0032] In this application, "A and B are each independently selected from x, y, or z" means that A and B are independent events, and the occurrence of event A does not affect the occurrence of event B. Therefore, when A is selected from x, B can be selected from any one of x, y, or z; when A is selected from y, B can be selected from any one of x, y, or z; when A is selected from z, B can be selected from any one of x, y, or z.
[0033] When a numerical range is disclosed in this application, the above range is considered continuous and includes the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when the range refers to integers, it includes each integer between the minimum and maximum values of the range. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed in this application should be understood to include any and all sub-ranges subsumed therein.
[0034] If there is no special instruction, all steps of this application can be carried out in sequence or randomly. For example, the method includes steps (a) and (b), which means that the method can include steps (a) and (b) carried out in sequence, or can also include steps (b) and (a) carried out in sequence. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method can include steps (a), (b), and (c) in sequence, or can also include steps (a), (c), and (b), or can also include steps (c), (a), and (b), etc.
[0035] In this application, "above" or "below" both include the number itself. For example, below 1 includes 1. Room temperature refers to 0°C to 60°C, including but not limited to 10°C to 40°C, or further 20°C to 30°C.
[0036] In this application, the percentage of breaking elongation is the ratio of the elongation length of the material at the time of stretching to fracture to the initial length, denoted by e or EB, with the unit of percentage (%). It characterizes the softness and elastic properties of the material. Generally speaking, the larger the percentage of breaking elongation, the better the softness and elasticity of the material. The test method for the percentage of breaking elongation of polyurethane is well-known to those skilled in the art, and this application does not limit it. Exemplarily, a universal tensile testing machine (also known as a universal material testing machine or tensile testing machine) can be used to test the tensile strength and percentage of breaking elongation of the sample.
[0037] In this application, the glass transition temperature (Tg) is an important indicator reflecting the flexibility or brittleness of polymers. A "soft monomer" refers to a monomer with a relatively low glass transition temperature of its homopolymer, which imparts certain flexibility and extensibility to the resin when participating in the copolymerization of the resin. Generally, a monomer with a homopolymer glass transition temperature of -20°C to -70°C is called a soft monomer. A "hard monomer" refers to a monomer with a relatively high glass transition temperature of its homopolymer, which can improve the hardness and tensile strength of the copolymer resin.
[0038] In this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, features defined with "first" and "second" may explicitly or implicitly include at least one of such features.
[0039] In this application, the meaning of "a plurality of" or "several" is at least two, such as two, three, etc., unless otherwise specifically defined. The meaning of "several" is at least one, such as one, two, three, etc., unless otherwise specifically defined. "At least one" means any one, any two, or any two or more. Unless otherwise mentioned, terms in the singular form may include the plural form and should not be construed as having a quantity of one.
[0040] In this application, for orientation terms, if there are terms such as "center", "lateral", "longitudinal", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", etc. indicating orientation and positional relationships, they are based on the orientation or positional relationships shown in the drawings. This is only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the indicated device or element must have a specific orientation, be constructed and operated in a specific orientation, and should not be construed as limiting the specific protection scope of this application.
[0041] When describing positional relationships, unless otherwise specified, when an element such as a layer, film, or substrate is referred to as being "on" another film layer, it can be directly on the other film layer or there may also be intermediate film layers. Further, when a layer is referred to as being "under" another layer, it can be directly below or there may be one or more intermediate layers. It can also be understood that when a layer is referred to as being "between" two layers, it can be the only layer between the two layers or there may also be one or more intermediate layers.
[0042] Galvanized steel sheets are widely used in the automotive, building materials, household appliances, and mechanical and electrical industries. However, traditional galvanized steel sheets are prone to white rust or even red rust during use. Moreover, most galvanized steel sheets need to be stamped into shape before being put on the market. For example, in the deep drawing process, problems such as cracking, powdering, and blackening of the galvanized layer are likely to occur during stamping, which affects the appearance quality, dimensional accuracy, and corrosion resistance of the formed parts.
[0043] To solve the above problems, the present application provides an aqueous chromium-free self-lubricating fingerprint-resistant coating, which, by weight percentage, comprises the following components: compounded polyurethane resin 15% - 32%, polyacrylic resin 10% - 23%, silane coupling agent 1% - 5%, filler 1% - 5%, compounds of molybdenum, vanadium, titanium, or zirconium 1% - 5%, leveling agent 0.1% - 0.5%, anti-scratch additive 1% - 5%, and water 24.5% - 70.9%; wherein, the compounded polyurethane resin is compounded from polyurethane resins with different elongation at break.
[0044] The molecular chains of the polyurethane with low elongation at break have limited movement and a relatively high crosslinking density, which endows the coating with higher hardness and rigidity. At the same time, the high crosslinked structure makes the coating surface denser, improving the wear resistance, chemical corrosion resistance, and scratch resistance of the coating. In addition, the polyurethane with low elongation at break can reduce the deformation of the coating caused by temperature or humidity changes, avoiding cracking. Moreover, the rigid coating matches better with low-elastic substrates (such as metals), has better adhesion, and can further reduce the peeling and paint loss of the coating caused by deformation differences. The molecular chains of the polyurethane with high elongation at break are longer, the crosslinking density is lower, and the intermolecular sliding ability is stronger. It can withstand large-scale stretching or bending without cracking, endowing the coating with high elasticity, flexibility, and low-temperature flexibility. And it can absorb impact energy through elastic deformation, reducing substrate damage and improving the impact resistance and deformation resistance of the coating. In addition, the flexible coating can deform synchronously with the expansion / contraction or vibration of the substrate, avoiding cracking or peeling caused by stress concentration. And the coating can still maintain integrity and function after frequent bending or stretching, showing excellent fatigue resistance and flexural fatigue resistance. In the present application, the compounded polyurethane with different elongation at break and the polyacrylic resin are used together as the main film-forming substances of the coating, which play a major role in corrosion resistance, impact resistance, tensile resistance, wear resistance, and scratch resistance on the surface of metals (such as galvanized steel sheets), improving the comprehensive performance of the coating. When this coating is used on the surface of passivated metal substrates, even after the deep drawing process, the metal workpiece still maintains a good appearance. Compared with the appearance of the processed surface and the unprocessed surface of the deep-drawn workpiece, there is no obvious change, maintaining its original color, and maintaining excellent corrosion resistance, wear resistance, and scratch resistance.
[0045] Understandably, by weight percentage, the waterborne chromium-free self-lubricating fingerprint-resistant coating described in this application includes 15% - 32% of a compounded polyurethane resin, including but not limited to 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 25%, 26%, 28%, 30%, 31% or 32%. Further, by weight percentage, the waterborne chromium-free self-lubricating fingerprint-resistant coating includes 15% - 28% of a compounded polyurethane resin.
[0046] In one embodiment, in the compounded polyurethane resin, the relationship between the elongation at break of each polyurethane raw material and its weight percentage presents a normal distribution. It can be understood that in a plane rectangular coordinate system, the x-axis is the elongation at break of the polyurethane raw material, the y-axis is the weight percentage of the corresponding polyurethane raw material in the compounded polyurethane resin, and the curve is a bell-shaped curve. Understandably, the normal distribution described in this application includes a standard normal distribution and a quasi-normal distribution. Among them, the quasi-normal distribution is similar in shape to the normal distribution but may have differences in some aspects (such as skewness, kurtosis, etc.). It usually retains some main characteristics of the normal distribution, such as unimodality, symmetry, etc., but may not fully conform to the strict definition of the normal distribution.
[0047] In one embodiment, by weight percentage of the compounded polyurethane resin, the compounded polyurethane resin includes the following components: 2% - 20% of a polyurethane with EB < 100%, 60% - 96% of a polyurethane with 100% ≤ EB ≤ 300%, and 2% - 20% of a polyurethane with EB > 300%.
[0048] In one embodiment, by weight percentage of the compounded polyurethane resin, the compounded polyurethane resin includes the following components: 2% - 20% of a polyurethane with EB < 100%, 20% - 50% of a polyurethane with 100% ≤ EB ≤ 200%, 20% - 50% of a polyurethane with 200% < EB ≤ 300%, and 2% - 20% of a polyurethane with EB > 300%.
[0049] In one embodiment, by weight percentage of the compounded polyurethane resin, the compounded polyurethane resin includes the following components: 5% - 20% of a polyurethane with EB < 100%, 20% - 45% of a polyurethane with 100% ≤ EB ≤ 200%, 20% - 45% of a polyurethane with 200% < EB ≤ 300%, and 5% - 20% of a polyurethane with EB > 300%.
[0050] In one embodiment, based on the weight percentage of the compounded polyurethane resin, the compounded polyurethane resin comprises the following components: 5% - 20% of polyurethane with EB < 100%, 20% - 45% of polyurethane with 100% ≤ EB ≤ 200%, 20% - 45% of polyurethane with 200% < EB ≤ 300%, and 5% - 20% of polyurethane with 300% < EB ≤ 400%.
[0051] In one embodiment, based on the weight percentage of the compounded polyurethane resin, the compounded polyurethane resin comprises the following components: 5% - 20% of polyurethane with EB < 100%, 10% - 25% of polyurethane with 100% ≤ EB ≤ 150%, 10% - 25% of polyurethane with 150% < EB ≤ 200%, 10% - 25% of polyurethane with 200% < EB ≤ 250%, 10% - 25% of polyurethane with 250% < EB ≤ 300%, and 5% - 20% of polyurethane with 300% < EB ≤ 400%.
[0052] It can be understood that the present application does not impose special restrictions on the types of polyurethanes. Optionally, the polyurethane can be selected from one or a combination of polyether - type polyurethanes, polyester - type polyurethanes, polyimide - type polyurethanes, and polyurea - type polyurethanes. Further, the present application does not impose special restrictions on the sources of polyurethanes, which can be self - made or purchased. Exemplarily, the polyurethanes in the present application can be selected from aqueous polyurethane products of companies such as Covestro, Tongtai Chemistry, Wanhua, Runchang Chemistry, Guanzhi, DIC, Oriental Yuhong, or Youmeite.
[0053] The preparation method of the compounded polyurethane resin of the present invention is simple in operation. It is only necessary to mix the polyurethane raw materials with different elongation at break directly.
[0054] It can be understood that, based on the weight percentage, the aqueous chromium - free self - lubricating fingerprint - resistant coating described in the present application comprises 10% - 23% of polyacrylic resin, including but not limited to 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, or 23%. Further, based on the weight percentage, the aqueous chromium - free self - lubricating fingerprint - resistant coating comprises 15% - 18% of polyacrylic resin.
[0055] In one embodiment, the polyacrylic resin is a copolymer formed by copolymerizing a hard monomer and a soft monomer in a weight ratio of 1:(0.2 - 5). The higher the Tg of the acrylic copolymer, the better the hardness of the coating and the stronger the scratch resistance; while the lower the Tg, the higher the molecular chain fluidity and the lower the viscosity of the resin emulsion, and the better the toughness of the coating. The acrylic copolymer formed by copolymerizing the hard monomer and the soft monomer has both strength and toughness, enabling the coating to have better scratch resistance, corrosion resistance and flexibility. By acting as the main film-forming substance of the coating together with the compounded polyurethane resin, it plays a major role in corrosion resistance, impact resistance, abrasion resistance and scratch resistance on the surface of metals (such as galvanized steel sheets). Further, in this application, acrylic copolymers with different Tgs are compounded (it can be two, three, four or more than four kinds), and together with the compounded polyurethane resin as the main film-forming substance of the coating, a denser protective film can be formed, further improving the tensile and impact resistance, corrosion resistance (such as salt spray resistance), acid and alkali resistance, solvent resistance and water resistance of the coating. Moreover, the acrylic copolymer can also cooperate with fillers to increase the abrasion resistance of the coating, and cooperate with leveling agents and anti-scratch aids to improve the scratch resistance of the coating. When the water-based chromium-free self-lubricating fingerprint-resistant coating of this application is used on the surface of passivated metal substrates, even after the deep drawing process, the metal workpiece still maintains a good appearance. Compared with the appearance of the processed surface and the unprocessed surface of the deep-drawn workpiece, there is no obvious change, maintaining the original color, and maintaining excellent corrosion resistance, abrasion resistance and scratch resistance.
[0056] In one embodiment, the hard monomer is selected from one or a combination of vinyl acetate, acrylonitrile, acrylamide, styrene, methyl methacrylate and methyl acrylate.
[0057] In one embodiment, the soft monomer is selected from one or a combination of ethyl acrylate, butyl acrylate and isooctyl acrylate.
[0058] In one embodiment, the polyacrylic resin includes acrylic polymer A with a high Tg and acrylic polymer B with a low Tg, and the weight ratio of acrylic polymer A to acrylic polymer B is 1:(0.5 - 2). Further, the acrylic polymer A is formed by reacting the above-mentioned hard monomer and soft monomer in a weight ratio of 1:(1 - 5), and the acrylic polymer B is formed by reacting the above-mentioned hard monomer and soft monomer in a weight ratio of 1:(0.2 - 1).
[0059] In one embodiment, the preparation method of the above acrylic polymer (acrylic polymer A or acrylic polymer B) includes the following steps:
[0060] Mix the hard monomer, soft monomer, acrylic acid, N-methylolacrylamide, crosslinking monomer and non-ionic emulsifier, and stir and disperse evenly to make a pre-emulsion;
[0061] Mix 5 wt% - 10 wt% of the pre - emulsion and 5 wt% - 10 wt% of the initiator, and react for 20 min - 40 min under the condition of 70°C - 85°C to prepare the seed emulsion;
[0062] When the seed emulsion turns blue, add 75 wt% - 85 wt% of the pre - emulsion and 75 wt% - 85 wt% of the initiator, and keep the reaction at 75°C - 90°C for 0.5 h - 1.5 h;
[0063] Add the remaining amount of the pre - emulsion and the initiator to the reaction system, and keep the reaction at 75°C - 90°C for 0.5 h - 1.5 h; Cool down to 50°C - 60°C, neutralize with ammonia water until the pH value of the system is 7 - 8, filter and discharge to obtain a milky white acrylic polymer with a slightly blue light.
[0064] In one of the embodiments, the cross - linking monomer is hydroxyethyl acrylate or hydroxypropyl acrylate.
[0065] In one of the embodiments, the initiator is ammonium persulfate. Further, the initiator is an aqueous solution of ammonium persulfate.
[0066] In this application, the silane coupling agent can chemically react with organic molecules (such as polyurethane, polyacrylate resin, leveling agent and anti - scratch additive) and inorganic molecules (such as fillers, compounds of molybdenum, vanadium, titanium or zirconium) in the water - borne chromium - free self - lubricating fingerprint - resistant coating to form stable chemical bonds, thereby improving the weather resistance and corrosion resistance of the coating. This enables the coating to better resist the erosion of natural factors such as sunlight, wind and rain in the outdoor environment, reduce the occurrence of problems such as fading, cracking and powdering, and is resistant to salt spray and chemicals, thus extending the service life of the coating; and the silane coupling agent can chemically react with the surface of the substrate (such as galvanized steel sheet) to form chemical bonds or physical adsorption, increasing the bonding force between the coating and the substrate, thereby improving the adhesion of the coating; and it plays a lubricating role in the coating, reducing the viscosity of the coating, making the coating easier to construct and apply; in addition, the silane coupling agent can also form a network structure in the interface layer between the coating and the substrate, further enhancing the cohesion of the coating and the stability against water erosion. It can be seen that the silane coupling agent cooperates synergistically with other components of the water - borne chromium - free self - lubricating fingerprint - resistant coating, which can improve the comprehensive performance of the coating. When this coating is used on the surface of passivated metal substrates, even after the deep - drawing process, the metal workpiece still maintains a good appearance. Compared with the appearance of the unprocessed surface of the deep - drawn workpiece, there is no obvious change, maintaining its original color, and maintaining excellent corrosion resistance, wear resistance and anti - scratch performance.
[0067] Understandably, based on weight percentage, the water-based chromium-free self-lubricating fingerprint-resistant coating described in this application includes 1% to 5% of a silane coupling agent, including but not limited to 1%, 2%, 3%, 4%, or 5%. Further, based on weight percentage, the water-based chromium-free self-lubricating fingerprint-resistant coating includes 2% to 5% of a silane coupling agent.
[0068] In one embodiment, the silane coupling agent is selected from one or a combination of more than one of an amino silane coupling agent, an epoxy silane coupling agent, and a vinyl silane coupling agent. Exemplarily, the silane coupling agent described in this application can be selected from one or a combination of more than one of KH-540, KH-550, KH-792, KH-560, and A-151.
[0069] In this application, the filler can improve the coating workability, such as rheology, and can also cooperate with other components in the coating. For example, through the action of the silane coupling agent, the filler is evenly filled in the network formed by the interpenetration of the compound polyurethane resin and the polyacrylate resin, supplementing the film-forming defects, and synergistically improving the corrosion resistance and mechanical properties of the coating (such as hardness, wear resistance, and impact resistance).
[0070] Understandably, based on weight percentage, the water-based chromium-free self-lubricating fingerprint-resistant coating described in this application includes 1% to 5% of a filler, including but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or 5%. Further, based on weight percentage, the water-based chromium-free self-lubricating fingerprint-resistant coating includes 1% to 3% of a filler.
[0071] In one embodiment, the filler includes nano-silica. Utilizing the high hardness and wear resistance of nano-silica, it can significantly improve the scratch resistance and abrasion resistance of the coating. Its high specific surface area and surface energy can also enhance the adhesion between the coating and the substrate, and can be used as a reinforcing material to improve the overall strength of the coating, and can also increase the rheological properties, density, and corrosion resistance of the coating, supplementing the surface film-forming defects to make the fingerprint-resistant coating more complete. Through the synergistic cooperation of nano-silica with other components in the water-based chromium-free self-lubricating fingerprint-resistant coating, the comprehensive performance of the coating is improved. When this coating is used on the surface of a passivated metal substrate, even after the deep drawing process, the metal workpiece still maintains a good appearance. Compared with the appearance of the processed surface and the unprocessed surface of the deep-drawn workpiece, there is no obvious change, maintaining the original color, and maintaining excellent corrosion resistance, wear resistance, and scratch resistance. Optionally, the particle size of the nano-silica is 5 nm to 100 nm. Further, the particle size of the nano-silica is 10 nm to 50 nm.
[0072] In the present application, the compounds of molybdenum, vanadium, titanium or zirconium can be in the form of metal oxides, metal sulfides or metal silicides, or in the form of salts. Exemplarily, the compounds of molybdenum can be selected from one or more combinations of sodium molybdate, ammonium molybdate, molybdenum disulfide, molybdenum trioxide, molybdenum silicide and nickel molybdate. Exemplarily, the compounds of vanadium can be selected from one or more combinations of vanadium pentoxide, vanadium dioxide, ammonium metavanadate and sodium metavanadate. Exemplarily, the compounds of titanium can be selected from one or more combinations of titanium dioxide, titanate, potassium fluotitanate, ammonium fluotitanate, titanium alloy and titanium nickel yellow. Exemplarily, the compounds of zirconium can be selected from one or more combinations of zirconium oxide, zirconium nitrate, zirconium silicate, zirconium phosphate and zirconium fluorosalt.
[0073] In the present application, the compounds of molybdenum, vanadium, titanium or zirconium can improve the adhesion of the coating to the substrate, corrosion resistance and scratch resistance. Specifically, (1) both the compounds of molybdenum and the compounds of vanadium can form a dense passivation film on the metal surface to prevent the corrosion medium (such as oxygen, water, chloride ions) from contacting the metal substrate, showing excellent corrosion inhibition; in addition, after the coating is scratched, both the molybdenum compound or the vanadium compound can react with water to generate new passivating substances to fill the scratches, thereby endowing the coating with certain self-healing ability and good adhesion; the compound of molybdenum (or the compound of vanadium) and the compound of titanium (or the compound of zirconium) are used in combination to form a composite passivation film, synergistically improving the corrosion resistance of the coating. (2) Both the compounds of titanium and the compounds of zirconium can be used for corrosion resistance. Some compounds can also form good chemical bonding with the metal surface, enhancing the adhesion of the coating, and the formed passivation film can effectively prevent the penetration of the corrosion medium, further improving the corrosion resistance of the coating; the compounds of titanium and the compounds of zirconium and the silane coupling agent are used in combination to form an organic-inorganic composite passivation film, which can improve the comprehensive performance of the coating, especially the corrosion resistance.
[0074] It can be understood that, by weight percentage, the aqueous chromium-free self-lubricating fingerprint-resistant coating described in the present application includes 1% to 5% of the compounds of molybdenum, vanadium, titanium or zirconium, including but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 5%. Further, by weight percentage, the aqueous chromium-free self-lubricating fingerprint-resistant coating includes 1% to 3% of the compounds of molybdenum, vanadium, titanium or zirconium.
[0075] It can be understood that in the present application, one of the compounds of molybdenum, the compounds of vanadium, the compounds of titanium and the compounds of zirconium can be used alone, or multiple combinations can be used in combination. In some of these embodiments, the compounds of molybdenum, the compounds of vanadium, the compounds of titanium and the compounds of zirconium are selected to be used alone. In some of these embodiments, two or more of the compounds of molybdenum, the compounds of vanadium, the compounds of titanium and the compounds of zirconium are selected to be used in combination.
[0076] In this application, the leveling agent can promote the formation of a flat, smooth, and uniform coating film during the drying and film-forming process of the coating, effectively reducing defects such as orange peel, brush marks, roller marks, floating color, and blooming on the surface of the coating film. It can also reduce the surface tension between the coating and the substrate, enabling the coating to better wet the substrate and reducing the surface tension gradient caused by solvent evaporation, thereby avoiding phenomena such as shrinkage holes, pinholes, and bubbles in the paint film, improving the integrity and density of the coating, making the appearance of the coating more beautiful, and enhancing the decorative effect. In addition, the leveling agent can also cooperate with other components to synergistically improve the adhesion and weather resistance of the coating, extend the service life of the coating film, and make the surface of the coating smoother, thereby improving the scratch resistance of the coating film.
[0077] It can be understood that, by weight percentage, the waterborne chromium-free self-lubricating fingerprint-resistant coating described in this application includes 0.1% - 0.5% of the leveling agent, including but not limited to 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, or 0.5%. Further, by weight percentage, the waterborne chromium-free self-lubricating fingerprint-resistant coating includes 0.1% - 0.3% of the silicone compound.
[0078] In one embodiment, the leveling agent includes polyether-modified silicone. In this application, polyether-modified silicone is used as the leveling agent. In addition to having the functions of the above leveling agent, it also has the effect of wetting the substrate. Additionally, polyether-modified silicone can also cooperate with the scratch-resistant additive to synergistically enhance the chemical corrosion resistance and smoothness of the coating, making the coating more suitable for applications requiring high smoothness, such as the automotive field.
[0079] In this application, the scratch-resistant additive forms a protective layer on the surface of the coating, increasing the hardness and wear resistance of the coating, thereby effectively reducing the visibility of scratches and abrasions and extending the service life of the coating. Moreover, the scratch-resistant additive can also significantly improve the leveling property and smoothness of the coating surface, reducing friction. Additionally, the scratch-resistant additive can enhance the chemical resistance and weather resistance of the coating, enabling it to still maintain good performance in harsh environments (such as high temperature, ultraviolet radiation, acid-base environment, etc.), and contributing to improving the flexibility and crack resistance of the coating, reducing cracks in the coating caused by temperature changes or mechanical stress, making the chromium-free fingerprint-resistant coating of this application particularly suitable for galvanized steel sheets and subsequent deep drawing processes.
[0080] It can be understood that, by weight percentage, the waterborne chromium-free self-lubricating fingerprint-resistant coating described in this application includes 1% - 5% of the scratch-resistant additive, including but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or 5%. Further, by weight percentage, the waterborne chromium-free self-lubricating fingerprint-resistant coating includes 1% - 3% of the scratch-resistant additive.
[0081] In one embodiment, the anti-scratch additive is compounded from anti-scratch additives with different particle sizes.
[0082] In one embodiment, the anti-scratch additive is composed of a first anti-scratch additive with a particle size of 0.1 μm to 0.5 μm and a second anti-scratch additive with a particle size of 1 μm to 3 μm in a weight ratio of 1:(1 - 2). It can be understood that the particle size of the first anti-scratch additive includes but is not limited to 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, or 0.5 μm. The particle size of the second anti-scratch additive includes but is not limited to 1 μm, 1.5 μm, 2 μm, 2.5 μm, or 3 μm. The anti-scratch additive with a large particle size has a lower specific gravity and can float on the surface of the coating to play an anti-scratch role. The specific gravity of the anti-scratch additive with a small particle size is close to that of the coating mixture and can penetrate the entire polymer network, imparting smoothness to the entire film layer during film formation. Through the compounding and synergy of anti-scratch additives with different particle sizes, the present application endows the entire chromium-free fingerprint-resistant coating with high smoothness, anti-scratch property, wear resistance, and corrosion resistance, thereby ensuring the secondary processing quality of metals (such as galvanized steel sheets).
[0083] In one embodiment, the anti-scratch additive is selected from one or a combination of polyethylene, polytetrafluoroethylene, polyethylene oxide, and silicone dispersions. It can be understood that the types of the first anti-scratch additive and the second anti-scratch additive are independent of each other and can be the same or different. Therefore, the first anti-scratch additive and the second anti-scratch additive are each independently selected from one or a combination of polyethylene, polytetrafluoroethylene, polyethylene oxide, and silicone dispersions.
[0084] In one embodiment, the anti-scratch additive is polyethylene wax. Utilizing the good chemical stability of polyethylene wax, it improves the corrosion resistance, water resistance, chemical resistance, and weather resistance of the coating. Moreover, polyethylene wax can form a protective layer on the surface of the coating film, significantly improving the anti-scratch property and wear resistance of the coating. And due to its low coefficient of friction, it can endow the coating film with excellent smoothness and has the effect of optimizing the rheological properties of the coating, improving the workability. Further, through the compounding of polyethylene wax with different particle sizes and the synergistic cooperation with other components in the coating, the comprehensive performance of the coating is improved, especially the corrosion resistance, anti-scratch property, and wear resistance of the coating. Applying this coating to the surface of a passivated metal substrate can significantly enhance the wear and corrosion resistance of the metal substrate (such as galvanized steel sheet), thereby ensuring the secondary processing quality of the galvanized steel sheet. It is particularly suitable for the deep drawing process and can enable the workpiece after deep drawing to still maintain a good appearance and excellent wear and corrosion resistance. It can be understood that the present application does not impose special restrictions on the source of polyethylene wax, which can be self-made or purchased. Exemplarily, the polyethylene wax described in the present application can be selected from the aqueous wax emulsion products of Longhai Chemical Industry, Yijiu Chemical Industry, or Wengkel.
[0085] Another object of the present application is to provide a method for preparing the above-mentioned waterborne chromium-free self-lubricating fingerprint-resistant coating, comprising the following steps:
[0086] Mix a compound polyurethane resin, a polyacrylic resin, a silane coupling agent, a filler, a compound of molybdenum, vanadium, titanium or zirconium, a leveling agent and an anti-scratch aid in water.
[0087] In one embodiment, the small-particle-size anti-scratch aid is added in portions, and through cyclic operations of stirring, stopping stirring and then restarting stirring, the instantaneous shear force is increased, so that the small-particle-size anti-scratch aid is fully dispersed in the mixture, and the smoothness of the coating is further improved during film formation.
[0088] In one embodiment, the method for preparing the above-mentioned waterborne chromium-free self-lubricating fingerprint-resistant coating comprises the following steps:
[0089] S100: Mix the compound polyurethane resin and the polyacrylic resin in water to prepare a first mixed solution;
[0090] S200: Under the condition of 40°C to 60°C, mix the silane coupling agent, the filler, the compound of molybdenum, vanadium, titanium or zirconium and the leveling agent with the first mixed solution to prepare a second mixed solution;
[0091] S300: Slowly add a first anti-scratch aid with a particle size of 0.1 μm to 0.5 μm to the second mixed solution, adding it in 2 to 5 portions, and stirring for 10 min to 15 min after each addition; after the addition of the small-particle-size anti-scratch aid is completed, add a second anti-scratch aid with a particle size of 1 μm to 3 μm in multiple portions, and continuously stir for 5 min to 10 min.
[0092] Furthermore, in steps S100 and S200, the stirring speed is 100 rpm to 120 rpm. In step S300, the stirring speed is 200 rpm to 500 rpm.
[0093] Another object of the present application is to provide a metal material, at least one surface of which is coated with a coating formed by the above-mentioned waterborne chromium-free self-lubricating fingerprint-resistant coating. Furthermore, the metal material is steel, galvanized steel sheet, galvanized alloy steel sheet, aluminized steel sheet, aluminum sheet, chemically treated galvanized steel sheet, chemically treated galvanized alloy steel sheet, chemically treated aluminized steel sheet, chemically treated aluminum sheet or PCM steel sheet. In one embodiment, the present application provides a galvanized steel sheet, at least one surface of which is coated with a coating formed by the above-mentioned waterborne chromium-free self-lubricating fingerprint-resistant coating. The galvanized steel sheet passivated by the chromium-free self-lubricating fingerprint-resistant coating has a good appearance. In addition, after testing, the galvanized steel sheet has excellent wear resistance, anti-scratch property, impact resistance, alkali resistance, solvent resistance and corrosion resistance.
[0094] Another object of the present application is to provide a deep-drawing workpiece, at least one surface of which is coated with a coating formed by the water-based chromium-free self-lubricating fingerprint-resistant coating as described above. The deep-drawing workpiece has a good appearance. Compared with the unprocessed surface, there is no obvious change in the appearance of the processed surface (deep-drawing surface), indicating that the film layer on the processed surface after deep-drawing is not damaged and can maintain its original color. In addition, after testing, both the processed surface and the unprocessed surface have excellent wear resistance, scratch resistance, alkali resistance, solvent resistance and corrosion resistance.
[0095] The technical solutions of the present application will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the following described embodiments are some embodiments of the present application, rather than all embodiments, and are only used to illustrate the present application and should not be regarded as limiting the scope of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present application. Those not specified in the embodiments are carried out under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments not specified by the manufacturer are all conventional products that can be obtained through commercial purchase.
[0096] Raw material description:
[0097] The description of the polyurethane raw materials is shown in Table 1 below.
[0098] Table 1 Description of polyurethane raw materials
[0099] 。
[0100] Silane coupling agent:
[0101] (1) Silane coupling agent A is KH-550;
[0102] (2) Silane coupling agent B is KH-560.
[0103] Silica: Commercially available nano-silica with a particle size of 10nm to 20nm.
[0104] Polyether-modified silicone:
[0105] (1) Polyether-modified silicone A: BYK-333 from BYK Chemie;
[0106] (2) Polyether-modified silicone B: BYK-300 from BYK Chemie.
[0107] Polyethylene wax:
[0108] (1) Polyethylene wax A: LHWAX®2140 wax emulsion with a particle size less than 0.2μm;
[0109] (2) Polyethylene wax B: LHWAX®H2040B wax emulsion, with a particle size less than 0.5 μm;
[0110] (3) Polyethylene wax C: TL-201C wax emulsion from Longkou Yijiu Chemical Technology Co., Ltd., with a particle size of 0.5 μm - 1 μm;
[0111] (4) Polyethylene wax D: LHWAX®2545 wax emulsion, with a particle size of 1 μm - 3 μm;
[0112] (5) Polyethylene wax E: LHWAX®2545B wax emulsion, with a particle size of 3 μm - 5 μm.
[0113] Example 1
[0114] This example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method, as follows:
[0115] (1) By weight percentage, the composition of the aqueous chromium-free self-lubricating fingerprint-resistant coating shown in this example is as follows: compound polyurethane resin 20%, polyacrylic resin 20%, silane coupling agent A 2%, silica 2%, molybdenum trioxide 3%, polyether-modified silicone A 0.3%, anti-scratch additive 3.2% and water 49.5%;
[0116] Among them, ① By weight percentage of the compound polyurethane resin, the composition of the compound polyurethane resin in this example is as follows: polyurethane with EB of 50% 10%, polyurethane with EB of 100% 20%, polyurethane with EB of 200% 20%, polyurethane with EB of 250% 20%, polyurethane A with EB of 300% 20% and polyurethane with EB of 350% 10%;
[0117] ② The polyacrylic resin in this example is compounded from acrylic polymer A with high Tg and acrylic polymer B with low Tg in a weight ratio of 1:1. Among them, acrylic polymer A is prepared by reacting vinyl acetate and ethyl acrylate in a weight ratio of 1:2, and acrylic polymer B is prepared by reacting vinyl acetate and ethyl acrylate in a weight ratio of 1:0.5; Further, the preparation method of acrylic polymer A or acrylic polymer B is as follows:
[0118] Mix vinyl acetate, ethyl acrylate, acrylic acid, N-methylol acrylamide, hydroxyethyl acrylate and non-ionic emulsifier, stir and disperse evenly to prepare a pre-emulsion; mix 10 wt% of the pre-emulsion and 10 wt% of the initiator ammonium persulfate, react at 80 °C for 30 min to prepare a seed emulsion; wait until the seed emulsion turns blue, add 80 wt% of the pre-emulsion and 80 wt% of the initiator, keep the temperature at 80 °C and react for 1 h; add the remaining pre-emulsion and initiator to the reaction system, keep the temperature at 80 °C and react for 1 h; cool down to 50 °C - 60 °C, neutralize with ammonia water until the pH value of the system is 7 - 8, filter and discharge to obtain a milky white acrylic polymer with a slightly blue light.
[0119] ③ The anti-scratch additive in this example is composed of LHWAX® 2140 polyethylene wax emulsion with a particle size less than 0.2 μm and LHWAX® 2545 polyethylene wax emulsion with a particle size of 1 μm - 3 μm in a weight ratio of 1:1.
[0120] (2)The preparation method of the waterborne chromium-free self-lubricating fingerprint-resistant coating in this example is as follows:
[0121] S100: Mix each polyurethane resin and polyacrylic resin with water, stir at a speed of 100 rpm for 10 min to prepare a first mixed solution;
[0122] S200: Under the conditions of 50 °C and stirring (rotation speed of 100 rpm), mix silane coupling agent A, silica, molybdenum trioxide and polyether-modified silicone A with the first mixed solution to prepare a second mixed solution;
[0123] S300: Slowly add small-particle-size polyethylene wax A to the second mixed solution, add it in 3 times during the period, and stir for 15 min (rotation speed of 300 rpm) after each addition; after adding all the small-particle-size polyethylene wax A, add large-particle-size polyethylene wax D in 3 times, continue to stir for 10 min (rotation speed of 300 rpm), and then fill and reserve.
[0124] Example 2
[0125] This example provides a waterborne chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Example 1 is the different dosages of some components, which are as follows:
[0126] By weight percentage, the composition of the waterborne chromium-free self-lubricating fingerprint-resistant coating in this example is as follows: compound polyurethane resin 25%, polyacrylic resin 20%, silane coupling agent A 3%, silica 3%, molybdenum trioxide 2%, polyether-modified silicone A 0.2%, anti-scratch additive 2.3% and water 44.5%.
[0127] Example 3
[0128] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the dosages of some components are different, specifically as follows:
[0129] By weight percentage, the composition of the aqueous chromium-free self-lubricating fingerprint-resistant coating in this embodiment is as follows: compound polyurethane resin 28%, polyacrylate resin 18%, silane coupling agent A 4%, silica 2%, molybdenum trioxide 1%, polyether-modified siloxane A 0.5%, anti-scratch additive 5% and water 41.5%.
[0130] Embodiment 4
[0131] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the dosages or grades of some components are different. Correspondingly, during the preparation of the coating, the corresponding raw materials are replaced, specifically as follows:
[0132] By weight percentage, the composition of the aqueous chromium-free self-lubricating fingerprint-resistant coating in this embodiment is as follows: compound polyurethane resin 20%, polyacrylate resin 18%, silane coupling agent B 4%, silica 5%, zirconia 4%, polyether-modified siloxane B 0.3%, anti-scratch additive 2% and water 46.7%.
[0133] Embodiment 5
[0134] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the grades of some polyurethane raw materials are changed. Correspondingly, during the preparation of the coating, the corresponding raw materials are replaced, specifically as follows:
[0135] By weight percentage of the compound polyurethane resin, the composition of the compound polyurethane resin in this embodiment is as follows: polyurethane with EB of 50% 10%, polyurethane with EB of 100% 20%, polyurethane with EB of 200% 20%, polyurethane with EB of 260% 20%, polyurethane B with EB of 300% 20% and polyurethane with EB of 350% 10%.
[0136] Embodiment 6
[0137] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the dosage of the polyurethane raw material is changed, resulting in a different composition of the compound polyurethane resin, specifically as follows:
[0138] By weight percentage of the compounded polyurethane resin, the composition of the compounded polyurethane resin in this example is as follows: 15% of polyurethane with EB of 50%, 25% of polyurethane with EB of 100%, 10% of polyurethane with EB of 200%, 10% of polyurethane with EB of 250%, 25% of polyurethane A with EB of 300%, and 15% of polyurethane with EB of 350%.
[0139] Example 7
[0140] This example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Example 1 is that the dosage of some polyurethane raw materials is changed, resulting in a different composition of the compounded polyurethane resin, which is specifically as follows:
[0141] By weight percentage of the compounded polyurethane resin, the composition of the compounded polyurethane resin in this example is as follows: 5% of polyurethane with EB of 50%, 15% of polyurethane with EB of 100%, 30% of polyurethane with EB of 200%, 25% of polyurethane with EB of 250%, 20% of polyurethane A with EB of 300%, and 5% of polyurethane with EB of 350%.
[0142] Example 8
[0143] This example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Example 1 is that the dosage or grade of some polyurethane raw materials is changed, and some polyurethane raw materials are omitted, resulting in a different composition of the compounded polyurethane resin, which is specifically as follows:
[0144] By weight percentage of the compounded polyurethane resin, the composition of the compounded polyurethane resin in this example is as follows: 10% of polyurethane with EB of 50%, 20% of polyurethane with EB of 100%, 30% of polyurethane with EB of 200%, 30% of polyurethane A with EB of 300%, and 10% of polyurethane with EB of 600%.
[0145] Example 9
[0146] This example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Example 1 is that the dosage of some polyurethane raw materials is changed and some polyurethane raw materials are omitted, resulting in a different composition of the compounded polyurethane resin, which is specifically as follows:
[0147] By weight percentage of the compounded polyurethane resin, the composition of the compounded polyurethane resin in this example is as follows: 10% of polyurethane with EB of 50%, 80% of polyurethane with EB of 200%, and 10% of polyurethane with EB of 350%.
[0148] Example 10
[0149] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the grades and dosages of some polyethylene wax emulsions are changed, resulting in different compositions of the compound anti-scratch additives. Correspondingly, during the preparation of the coating, the corresponding raw materials are replaced, as follows:
[0150] In this embodiment, the anti-scratch additive is composed of LHWAX® H2040B polyethylene wax emulsion with a particle size less than 0.5 μm and LHWAX® 2545 polyethylene wax emulsion with a particle size of 1 μm to 3 μm in a weight ratio of 1:1.5.
[0151] Embodiment 11
[0152] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the grades of some polyethylene wax emulsions are changed, resulting in different compositions of the compound anti-scratch additives. Correspondingly, during the preparation of the coating, the corresponding raw materials are replaced, as follows:
[0153] In this embodiment, the anti-scratch additive is composed of TL-201C polyethylene wax emulsion with a particle size of 0.5 μm to 1.0 μm and LHWAX® 2545 polyethylene wax emulsion with a particle size of 1 μm to 3 μm in a weight ratio of 1:1.
[0154] Embodiment 12
[0155] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the grades of some polyethylene wax emulsions are changed, resulting in different compositions of the compound anti-scratch additives. Correspondingly, during the preparation of the coating, the corresponding raw materials are replaced, as follows:
[0156] In this embodiment, the anti-scratch additive is composed of LHWAX® 2140 polyethylene wax emulsion with a particle size less than 0.2 μm and LHWAX® 2545B polyethylene wax emulsion with a particle size of 3 μm to 5 μm in a weight ratio of 1:1.
[0157] Embodiment 13
[0158] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Embodiment 1 is that the anti-scratch additive is not used in a compound manner. Correspondingly, during the preparation of the coating, the corresponding raw materials are omitted, as follows:
[0159] In this embodiment, the anti-scratch additive is LHWAX® 2140 polyethylene wax emulsion with a particle size less than 0.2 μm.
[0160] Embodiment 14
[0161] This embodiment provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and a preparation method thereof. The main difference from Embodiment 1 is that the anti-scratch aids are not used in combination. Correspondingly, in the process of preparing the coating, the corresponding raw materials are omitted, as follows:
[0162] In this embodiment, the anti-scratch aid is LHWAX® 2545 polyethylene wax emulsion with a particle size of 1 μm to 3 μm.
[0163] Comparative Example 1
[0164] This comparative example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and a preparation method thereof. The main difference from Embodiment 1 is that the polyurethane resin is not used in combination. Correspondingly, in the process of preparing the coating, the corresponding raw materials are omitted, as follows:
[0165] In this comparative example, the polyurethane resin is a polyurethane with an elongation at break of 100%.
[0166] Comparative Example 2
[0167] This comparative example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and a preparation method thereof. The main difference from Embodiment 1 is that the polyurethane resin is not used in combination. Correspondingly, in the process of preparing the coating, the corresponding raw materials are omitted, as follows:
[0168] In this comparative example, the polyurethane resin is a polyurethane with an elongation at break of 300%.
[0169] Comparative Example 3
[0170] This comparative example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and a preparation method thereof. The main difference from Embodiment 1 is that the polyurethane resin is not used in combination. Correspondingly, in the process of preparing the coating, the corresponding raw materials are omitted, as follows:
[0171] In this comparative example, the polyurethane resin is a polyurethane with an elongation at break of 600%.
[0172] Comparative Example 4
[0173] This comparative example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and a preparation method thereof. The main difference from Embodiment 1 is that the amounts of some components are different, as follows:
[0174] In terms of weight percentage, the composition of the aqueous chromium-free self-lubricating fingerprint-resistant coating shown in this comparative example is as follows: compounded polyurethane resin 10%, polyacrylic resin 20%, silane coupling agent A 3%, silicon dioxide 3%, molybdenum trioxide 2%, polyether-modified silicone A 0.2%, anti-scratch aid 2.3% and water 59.5%.
[0175] Comparative Example 5
[0176] This comparative example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Example 1 is the different dosages of some components, which are as follows:
[0177] By weight percentage, the composition of the aqueous chromium-free self-lubricating fingerprint-resistant coating shown in this comparative example is as follows: compound polyurethane resin 40%, polyacrylic resin 20%, silane coupling agent A 5%, silica 4%, molybdenum trioxide 1%, polyether-modified silicone A 1%, scratch-resistant additive 2%, and water 27%.
[0178] Comparative Example 6
[0179] This comparative example provides an aqueous chromium-free self-lubricating fingerprint-resistant coating and its preparation method. The main difference from Example 1 is the different dosages of some components, which are as follows:
[0180] By weight percentage, the composition of the aqueous chromium-free self-lubricating fingerprint-resistant coating shown in this comparative example is as follows: compound polyurethane resin 30%, polyacrylic resin 7%, silane coupling agent A 2%, silica 3%, molybdenum trioxide 1%, polyether-modified silicone A 0.2%, scratch-resistant additive 1%, and water 55.8%.
[0181] Detection test
[0182] Select 20 galvanized steel plates of the same size and shape (numbered 1 - 20), and use the aqueous chromium-free self-lubricating fingerprint-resistant coatings prepared in equal amounts from Examples 1 - 14 and Comparative Examples 1 - 6 to perform surface passivation treatment on the galvanized steel plates, obtaining 20 groups of galvanized steel plates with surface passivation treatment; another 20 galvanized steel plates coated with the aqueous chromium-free self-lubricating fingerprint-resistant coatings prepared in Examples 1 - 14 and Comparative Examples 1 - 6 (numbered 21 - 40) are subjected to deep drawing treatment through a high-speed deep drawing testing machine and a special mold, and the stress deformation area is used as the processing surface, and the non-stamped surface is used as the unprocessed surface. The passivated surfaces of the galvanized steel plates numbered 1 - 20 and the processed and unprocessed surfaces of the deep drawing workpieces numbered 21 - 40 are evaluated using the following methods. The test results are shown in Table 2 and Table 3 and Figures 1 to 5 .
[0183] 1. Appearance
[0184] Observe the appearance of the surface of the galvanized steel plate after passivation treatment and the processed and unprocessed surfaces of the deep drawing workpiece with the naked eye. The evaluation criteria are as follows: Grade I: The coating is continuous, uniform, smooth, flat, and has no traces; Grade II: The coating surface has traces observable by the naked eye (tensile marks, indentations, or scratches); Grade III: The coating is broken or there are obvious traces on the surface, such as friction black lines.
[0185] 2. Alkaline resistance
[0186] The surfaces of the passivated galvanized steel sheets, the processed and unprocessed surfaces of the deep-drawn workpieces were immersed in a 2% sodium hydroxide solution (w%) at 60 °C for 2 minutes, then rinsed with water and dried, and the surface appearance changes were observed with the naked eye. The evaluation criteria are as follows: Grade I: There are no traces on the coating surface; Grade II: There are corrosion white spots observable with the naked eye on the coating surface; Grade III: The coating starts to dissolve or peel off.
[0187] 3. Solvent resistance
[0188] The reagent used was an 80% ethanol solution (v%). After impregnating gauze with it, the surfaces of the passivated galvanized steel sheets, the processed and unprocessed surfaces of the galvanized steel workpieces after deep drawing were rubbed back and forth 10 times with a pressure of 0.5 kg, and then the surface appearance changes were visually observed and evaluated. The evaluation criteria are as follows: Grade I: There are no traces on the wiped part; Grade II: There are traces observable with the naked eye on the wiped part; Grade III: There are obvious white traces on the wiped part, and the coating starts to dissolve and the bottom can be seen.
[0189] 4. Corrosion resistance
[0190] Salt spray tests (JIS Z 2371) were carried out on the surfaces of the passivated galvanized steel sheets, the processed and unprocessed surfaces of the galvanized steel workpieces after deep drawing. 1. Visually measure the white rust resistance of the galvanized steel sheets, and evaluate the time when the white rust area reaches 5%, in hours; 2. Visually measure the red rust resistance of the processed surface of the deep-drawn workpiece, and evaluate the time when the red rust area reaches 5%, in hours; 3. Visually measure the white rust resistance of the unprocessed surface of the deep-drawn workpiece, and evaluate the time when the white rust area reaches 5%, in hours.
[0191] 5. Impact resistance
[0192] The surface of the passivated galvanized steel sheet was impacted by an impact tester (≥50 kg / cm), and the situation of the coating surface was observed. The evaluation criteria are as follows: Grade I: There are no traces on the impacted part; Grade II: There are traces observable with the naked eye on the impacted part; Grade III: There are obvious traces on the impacted part and cracks appear.
[0193] 6. Scratch resistance
[0194] HB erasers with a load of 500 g were used to rub the surfaces of the passivated galvanized steel sheets, the processed and unprocessed surfaces of the galvanized steel workpieces after deep drawing back and forth 10 times, and the surface appearance changes were visually observed and evaluated. The evaluation criteria are as follows: Grade I: There are no traces on the rubbed part; Grade II: There are traces observable with the naked eye on the rubbed part; Grade III: There are obvious white traces on the rubbed part and cracks appear.
[0195] Table 2 Effect data of fingerprint-resistant coatings on passivating the surfaces of galvanized steel sheets using Examples 1-14 and Comparative Examples 1-6
[0196] .
[0197] Table 3 Effect data of the surface of the fingerprint-resistant coated passivated galvanized steel sheet after further deep drawing using Examples 1-14 and Comparative Examples 1-6
[0198] .
[0199] In addition, Figure 1 is the effect diagram of the passivated galvanized steel sheet with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 2 of the present application. It can be seen from Figure 1 that the galvanized steel sheet passivated by the chromium-free self-lubricating fingerprint-resistant coating has a good appearance.
[0200] Figure 2 is the effect diagram of the passivated galvanized steel sheet with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 1 of the present application after the deep drawing process. It can be seen from Figure 2 that the deep-drawn workpiece has a good appearance. Compared with the unprocessed surface, there is no obvious change in the appearance of the processed surface (deep-drawn surface), indicating that the film layer on the processed surface after deep drawing is not damaged and can maintain its original color.
[0201] Figure 3 is the effect diagram of the passivated galvanized steel sheet with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 1 of the present application after 120 h of salt spray test. It can be seen from Figure 3 that the coating prepared in Example 1 can efficiently passivate the surface of the galvanized steel sheet and significantly improve its corrosion resistance.
[0202] Figure 4 is the effect diagram of the passivated galvanized steel workpiece with the water-based chromium-free self-lubricating fingerprint-resistant coating in Example 1 of the present application after the deep drawing process and 96 h of salt spray test in sequence. Figure 4 In (A) is the effect diagram without salt spray test, Figure 4 in (B) is the effect diagram after 96 h of salt spray test. It can be seen from Figure 4 that the coating prepared in Example 1 can efficiently passivate the surface of the galvanized steel, improve its corrosion resistance, scratch resistance and impact resistance, and make the workpiece after deep drawing still maintain excellent corrosion resistance.
[0203] Figure 5 is the effect diagram of the passivated galvanized steel workpiece with the water-based chromium-free self-lubricating fingerprint-resistant coating in Comparative Example 2 of the present application after the deep drawing process and 96 h of salt spray test in sequence. After deep drawing, the surface coating of the workpiece is damaged and the appearance is blackened. After 96 h of salt spray test, a large amount of white rust and red rust appear on both the processed surface and the unprocessed surface. It can be seen from Figure 5It can be seen that Comparative Example 2 only uses a polyurethane resin with a single elongation at break, and the coating has poor impact resistance. It is difficult to balance stretching and adhesion during deep drawing, and it cannot effectively passivate galvanized steel, making it prone to rust. White rust and red rust quickly appear in the salt spray test.
[0204] Combined with Tables 2 to 3 and Figures 1 to 5 It can be seen that compared with Comparative Examples 1 to 3 that use a single elongation at break of polyurethane, the amount of compounded polyurethane resin in Comparative Example 4 is too small, the amount of compounded polyurethane resin in Comparative Example 5 is too large, and the amount of polyacrylic acid resin in Comparative Example 6 is too small. In Examples 1 to 14 of the present application, a compounded polyurethane resin, polyacrylic acid resin, silane coupling agent, filler, compounds of molybdenum, vanadium, titanium or zirconium, leveling agent, anti-scratch additive and water are used in combination, and the amounts of each component are reasonably controlled. The comprehensive performance of the provided water-based chromium-free self-lubricating fingerprint-resistant coating is more excellent. When it is used on the surface of a passivated galvanized steel sheet, the appearance is good, and it can significantly enhance the alkali resistance, solvent resistance, corrosion resistance, impact resistance, wear resistance and anti-scratch performance of the galvanized steel sheet. Moreover, this fingerprint-resistant coating can enable the workpiece of the galvanized steel sheet after deep drawing to still maintain a good appearance and excellent alkali resistance, solvent resistance, corrosion resistance, wear resistance and anti-scratch performance.
[0205] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered to be within the scope described in this specification.
[0206] The above-described embodiments only represent several implementation manners of the present application, which are convenient for understanding the technical solutions of the present application specifically and in detail, but should not be construed as a limitation on the protection scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present application, several deformations and improvements can still be made, and these all belong to the protection scope of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments based on the technical solutions provided by the present application are all within the protection scope of the appended claims of the present application. Therefore, the protection scope of the patent of the present application should be subject to the content of the appended claims, and the description and drawings can be used to explain the content of the claims.
Claims
1. A water-based chromium-free self-lubricating fingerprint-resistant coating, characterized in that, Comprising the following components by weight percentage: compounded polyurethane resin 15% - 32%, polyacrylic resin 10% - 23%, silane coupling agent 1% - 5%, filler 1% - 5%, compound of molybdenum, vanadium, titanium or zirconium 1% - 5%, leveling agent 0.1% - 0.5%, anti-scratch aid 1% - 5% and water 24.5% - 70.9%; wherein, the compounded polyurethane resin is compounded from polyurethane resins with different elongation at break.
2. The aqueous chromium-free self-lubricating fingerprint-resistant coating according to claim 1, characterized in that, In the compounded polyurethane resin, the relationship between the elongation at break of each polyurethane raw material and its weight percentage presents a normal distribution.
3. The aqueous chromium-free self-lubricating fingerprint-resistant coating according to claim 1, characterized in that, Denoting the elongation at break as EB, by weight percentage of the compounded polyurethane resin, the compounded polyurethane resin comprises the following components: polyurethane with EB < 100% 2% - 20%, polyurethane with 100% ≤ EB ≤ 200% 20% - 50%, polyurethane with 200% < EB ≤ 300% 20% - 50% and polyurethane with EB > 300% 2% - 20%.
4. The aqueous chromium-free self-lubricating fingerprint-resistant coating according to claim 1, wherein The anti-scratch aid is compounded from anti-scratch aids with different particle sizes.
5. The water-based chromium-free self-lubricating fingerprint-resistant coating according to claim 4, wherein The anti-scratch aid satisfies one or more of the following (1) - (2): (1) The anti-scratch aid is composed of a first anti-scratch aid with a particle size of 0.1 μm - 0.5 μm and a second anti-scratch aid with a particle size of 1 μm - 3 μm in a weight ratio of 1:(1 - 2); (2) The anti-scratch aid is selected from one or more combinations of polyethylene, polytetrafluoroethylene, oxidized polyethylene and silicone dispersion.
6. The water-based chromium-free self-lubricating fingerprint-resistant coating according to any one of claims 1 to 5, characterized in that The polyacrylic resin is a copolymer, copolymerized from a hard monomer and a soft monomer in a weight ratio of 1:(0.2 - 5).
7. The aqueous chromium-free self-lubricating fingerprint-resistant coating according to any one of claims 1 to 5, characterized in that, Satisfying one or more of the following (1) - (3): (1) The silane coupling agent is selected from one or more combinations of amino silane coupling agent, epoxy silane coupling agent and vinyl silane coupling agent; (2) The filler includes nano-silica; (3) The leveling agent includes polyether modified silicone.
8. A preparation method of the water-based chromium-free self-lubricating fingerprint-resistant coating according to any one of claims 1 to 7, characterized in that, Including the following steps: Mix the compounded polyurethane resin, polyacrylic resin, silane coupling agent, filler, compound of molybdenum, vanadium, titanium or zirconium, leveling agent and anti-scratch aid in water.
9. A metal material, characterized in that, At least one surface of the metal material is coated with a coating formed by the waterborne chromium-free self-lubricating fingerprint-resistant coating according to any one of claims 1 - 7.
10. A deep-drawing workpiece, characterized in that, At least one surface of the deep-drawing workpiece is coated with a coating formed by the waterborne chromium-free self-lubricating fingerprint-resistant coating according to any one of claims 1 - 7.
Citation Information
Cited By
Special chromium-free fingerprint-resistant coating with self-repairing function for high aluminum, zinc, aluminum and magnesium
CN120648361A